Functional redundancy between glucocorticoid and mineralocorticoid receptors in mature corticotropin-releasing hormone neurons protects from obesity - Liu, Yu; Lin, Dongfa; Najam, Syeda Sadia; Huang, Shangyuan; Song, Muyi; Sirakawin, Chaweewan; Zhao, Catherine; Jiang, Haixia; Konopka, Witold; Herzig, Stephan; Vinnikov, Ilya A. (Obesity, 2024)
Objective Here, we aimed to investigate the role of glucocorticoid and mineralocorticoid receptors (GRs and MRs, respectively) in the regulation of energy homeostasis. Methods We used three mouse models with simultaneous deletion of GRs and MRs in either forebrain neurons, the paraventricular nucleus, or corticotropin-releasing hormone (CRH) neurons and compared them with wild-type controls or isolated knockout groups. In addition to body weight, food intake, energy expenditure, insulin sensitivity, fat/lean mass distribution, and plasma corticosterone levels, we also performed transcriptomic analysis of CRH neurons and assessed their response to melanocortinergic stimulation. Results Similar to global double-knockout models, deletion of GRs and MRs specifically in mature CRH neurons resulted in obesity. Importantly, the latter was accompanied by insulin resistance, but not increased plasma corticosterone levels. Transcriptomic analysis of these neurons revealed upregulation of several genes involved in postsynaptic signal transduction, including the Ptk2b gene, which encodes proline-rich tyrosine kinase 2. Knockout of both nuclear receptors leads to upregulation of Ptk2b in CRH neurons, which results in their diminished responsiveness to melanocortinergic stimulation. Conclusions Our data demonstrate the functional redundancy of GRs and MRs in CRH neurons to maintain energy homeostasis and prevent obesity. Simultaneous targeting of both receptors might represent an unprecedented approach to counteract obesity.
Online veröffentlicht: 24. September 2024
Gesehen am 02.04.2025